Adsorption of copper(II) and lead(II) ions from aqueous solutions by porcellanite - Hmood, A.Y.; Jassim, T.E. (Mesopotamian Journal of Marine Sciences, 2022)
This work is concerned with one of the applications of adsorption behavior from aqueous solution. It deals with the adsorption of copper (II) and lead (II) ions on the surface of porcellanite, which is locally available in Iraq. The purpose of this study is to search for surfaces that are highly applicable for copper (II) and lead (II) ions adsorption to treat the pollution of aqueous solution in nature. The different variables affecting the adsorption capacity of the porcellanite such as contact time, initial metal ion concentration in the feed solution, pH of the medium and temperature, were investigated on a batch process mode. The optimum contact time to attain equilibrium is 90 min for copper (II) ion, 30 min for lead (II) ion, and the pH values in the range of 2-10. The results showed the optimum pH for Cu(II) is 8 and for Pb(II) is 4. The experimental data of adsorption were fitted to two different isotherms, namely; Langmuir and Freundlich. These isotherms equations were applied at different temperatures. The results obtained showed that, the Langmuir isotherm equation is better fitted to the experimental data than the Freundlich isotherm equation. The thermodynamic parameters indicated that ΔH was endothermic, ΔG was a spontaneous process and ΔS was positive value.